2020
DOI: 10.1055/s-0040-1702171
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Trauma-Induced Coagulopathy by Viscoelastography

Abstract: This article explores the application of viscoelastic tests (VETs) in trauma-induced coagulopathy and trauma resuscitation. We describe the advantages of VETs over conventional coagulation tests in the trauma setting and refer to previous disciplines in which VET use has reduced blood product utilization, guided prohemostatic agents, and improved clinical outcomes such as the mortality of critically bleeding patients. We describe different VETs and provide guidance for blood component therapy and prohemostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 112 publications
(162 reference statements)
0
67
0
2
Order By: Relevance
“…11,12 However, a large number of such studies already demonstrated that rotational thromboelastometry (ROTEM) can detect fibrin clot formation abnormalities, eg, factor XIII (FXIII) deficiency and abnormal fibrinolysis, eg, hyperfibrinolysis in trauma patients. [13][14][15] The test is validated and widely used in hospital laboratories. We added exogenous t-PA to improve the sensitivity of the test to hypofibrinolysis and reported the intra-and inter-assay precision of the modified assay in our hands.…”
Section: Response To "Studies On Hemostasis In Covid-19 Deserve Carefmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 However, a large number of such studies already demonstrated that rotational thromboelastometry (ROTEM) can detect fibrin clot formation abnormalities, eg, factor XIII (FXIII) deficiency and abnormal fibrinolysis, eg, hyperfibrinolysis in trauma patients. [13][14][15] The test is validated and widely used in hospital laboratories. We added exogenous t-PA to improve the sensitivity of the test to hypofibrinolysis and reported the intra-and inter-assay precision of the modified assay in our hands.…”
Section: Response To "Studies On Hemostasis In Covid-19 Deserve Carefmentioning
confidence: 99%
“…The debate on the performance of different global hemostasis assays in different clinical settings is still open and needs more information from clinical studies 11,12 . However, a large number of such studies already demonstrated that rotational thromboelastometry (ROTEM) can detect fibrin clot formation abnormalities, eg, factor XIII (FXIII) deficiency and abnormal fibrinolysis, eg, hyperfibrinolysis in trauma patients 13‐15 . The test is validated and widely used in hospital laboratories.…”
mentioning
confidence: 99%
“…Viscoelastic monitoring using thromboelastography (TEG) is well positioned to quickly assess a patient’s coagulation profile—initial results can be obtained in as little as 10 min with full results available after 30–60 min directly at the site of care [ 29 , 30 , 31 , 32 ]. TEG is also able to guide hemostatic replacement according to individual patient needs [ 21 ] and has an advantage over conventional coagulation tests in the treatment of trauma [ 20 ]. As a result, use of TEG has been associated with improved patient outcomes, particularly reduction in mortality as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the TEG ® 6s Hemostasis Analyzer (Haemonetics Corp., Boston, MA, USA), testing is available at the site of care providing rapid, individual patient coagulation assessment. Viscoelastic assays are thought to be more reliable than conventional clotting tests, providing a more accurate and rapid assessment of coagulopathy that is more predictive of massive transfusion needs [ 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Hartman et al then provided an in-depth description of viscoelastic methods involving the thromboelastography and rotational thromboelastometry. 3 Trauma creates a broad spectrum of abnormal physiology, with a wide range of tissue injury and blood pressures ranging from hypertensive to asystole. Therefore, it is not surprising that a spectrum of coagulation changes is present when these severely injured patients present to the emergency department.…”
mentioning
confidence: 99%